Morfologi Koloni Bakteri Endofit dari Akar Tanaman Kopi Arabika - Maulana, Mizan; Safriani, Suri Raihan; Ritaqwin, Zaitun (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
Many endophytic bacteria live inside and outside healthy plant tissue, including coffee plants. Each type of plant in a different region certainly has different types of endophytic bacteria. This research aims to isolate endophytic bacteria from the roots of coffee plants taken from one of the community's coffee plantations in Dedamar Village, Bintang District, Central Aceh at an altitude of 1200 meters above sea level. Isolation was carried out by taking 100 ml samples of rinsed and crushed coffee roots and spreading them on NA media. Then incubating them for 24 hours so that the bacteria could grow and develop. There was 1 isolate of endophytic bacteria that was successfully isolated from the roots of coffee plants.